(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The point of the present investigation is to evaluate the groundwater quality of Lefunga block, west Tripura locale, Tripura, for irrigation and residential purposes. Nine examples were gathered from bore wells utilized for drinking and irrigation purposes. The water tests were examined for real cations like calcium, magnesium, sodium, potassium, iron and anions like chloride, bi-carbonate and sulfate. Tests were additionally examined for arsenic and fluoride focus. The imperative constituents that impacts water quality for irrigation, for example, Electrical conductivity (EC), Total Dissolved Solids (TDS), Sodium Adsorption Ratio (SAR), Magnesium Adsorption Ratio (MAR), Soluble Sodium Percentage (SSP) and Permeability Index (PI) were resolved and contrasted and standard points of confinement. The estimations of TDS run from 29.33 - 86.00 mgL, SAR values run from 0.04 – 0.07, MAR esteems extend from 33.56 – 53.68 and SSP go from 3.01 - 5.87. Results demonstrate that they all exist in as far as possible and in this way largely appropriate for irrigation reason. Thus, the groundwater of this region is free from saltiness danger and has no antagonistic impact on soil properties. The got diagnostic information of water tests in Lefunga block propose that the quality of water is inside the standard furthest reaches of WQI order and satisfactory for drinking purposes both in pre and post with the exception of one area having abnormal state of iron substance. Besides, the water tests additionally fall inside suggested restrains and are discovered appropriate for drinking purposes with the exception of one example having large amounts of iron and along these lines rendering it to be extremely poor for drinking purposes according to WQI grouping.